Transcriptomic analysis of the TRP gene family in human brain physiopathology - Olejniczak, Barbara; Balakrishnan, Arpita; Augustyniak, Justyna; Salińska, Elżbieta; Bronisz, Agnieszka; Godlewski, Jakub (Frontiers in Molecular Neuroscience, 2025)
The transient receptor potential (TRP) gene family is vital to cellular physiology, mediating ion flow across membranes and facilitating sensory signal transduction. This article examines the transcriptomic landscape of TRP genes, emphasizing their varying expression across organs, tissues, and cells, with a particular focus on the brain. Analysis reveals a distinct spatial distribution of TRP gene expression, notably enriched in the hippocampus during brain development, highlighting their essential role in neuronal function. Utilizing datasets from the Human Protein Atlas, Allen Human Brain Atlas, and studies on aging and dementia, associations are identified between TRP gene expression and the development or pathophysiology of neural tissue, highlighting the therapeutic potential of TRP channels in addressing, e.g., sensory impairments and cognitive decline. These insights into the regulatory dynamics of TRP channels lay a foundation for developing targeted interventions for neurodegenerative disorders.